The Broken Helix: innovation and the political-economic crisis in Brazil - de Jesus, Diego Santos Vieira; Kamlot, Daniel (Seven Editora, 2023)
The aim of this article is to explain how the political-economic crisis in Brazil in the second half of the 2010s affected the cooperation between government, industries and universities in promoting innovation in the country. Based on the theoretical framework of Leydesdorff & Etzkowitz (1998), the central argument points out that the budget crisis and allegations of corruption created limits to cooperation among these actors and reinforced the structural obstacles in their relationship in Brazil. The qualitative methodology applied in this research is the case study, which allows to verify whether the path between the hypothetical causes – the budgetary crisis and corruption – and the observed effect – the reduction of collaboration between government, companies/industries and universities in the promotion of innovation – behaved as planned by theoretical-conceptual discussion presented. DOI: https://doi.org/10.56238/methofocusinterv1-089